Pachycerianthus (Ceriantharia) from British Columbia and Washington - Arai, M. N. (Journal of the Fisheries Research Board of Canada, 1971)
Pachycerianthus fimbriates specimens from seven collecting areas are described. Many of these specimens closely resemble Pachycerianthus torreyi Arai 1965 from California, but the range of variation is wider. Pachycerianthus torreyi and Pachycerianthus plicatus are considered junior synonyms of P. fimbriatus.